COLOURFUL DIET FOR GOOD HEALTH - Gupta, Vandana (International Journal of Research -GRANTHAALAYAH, 2014)
We are surrounded by colour and they can affect us profoundly and in ways that we may not have thought of. It is a known fact, that colours can influence your moods, feelings and emotions. Colours influence your actions and how you respond to people, situations and ideas. Apart from the colour of interiors, exteriors, our clothing and other things, the colour of food and beverage products are also extremely important. Green fruits and vegetables support eye health and may help protect against certain types of cancer. Orange and yellows fruits and vegetables are high in Vitamins C and B/foliate which may reduce risk of birth defects. Red fruits and vegetables protect the cells from free radical damage and healthy for the heart. Blue and purple fruits and vegetables may help reduce the risk of cancer, stroke, heart disease, memory decline and aging-related diseases. White fruits and vegetables may lower cholesterol and blood pressure as well as reduce risks of stomach cancer and heart disease. Therefore to keep ourselves in good health we should get a range of fruits and vegetables in varying hues over the course of a week.